2014
DOI: 10.1016/j.tem.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

G protein-coupled receptors and the regulation of autophagy

Abstract: Autophagy is an important catabolic cellular process that eliminates damaged and unnecessary cytoplasmic proteins and organelles. Basal autophagy occurs during normal physiological conditions, but the activity of this process can be significantly altered in human diseases. Thus, defining the regulatory inputs and signals that control autophagy is essential. Nutrients are key modulators of autophagy. While autophagy is generally accepted to be regulated in a cell autonomous fashion, recent studies suggest nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 103 publications
0
66
0
1
Order By: Relevance
“…Despite mounting evidence for a causal role of autophagy suppression in the promotion of compensatory hypertrophy (4,11,31,(42)(43)(44)(45)(46), the mechanistic links between pressure overload and adrenergic signaling-induced autophagic suppression have remained largely unsolved. A prior report indicated that endothelin-1 can suppress autophagy by inducing ubiquitination and degradation of Atg14L through ZBTB16-Cullin3-Rock1 E3 ubiquitin ligase complex (47).…”
Section: Discussionmentioning
confidence: 99%
“…Despite mounting evidence for a causal role of autophagy suppression in the promotion of compensatory hypertrophy (4,11,31,(42)(43)(44)(45)(46), the mechanistic links between pressure overload and adrenergic signaling-induced autophagic suppression have remained largely unsolved. A prior report indicated that endothelin-1 can suppress autophagy by inducing ubiquitination and degradation of Atg14L through ZBTB16-Cullin3-Rock1 E3 ubiquitin ligase complex (47).…”
Section: Discussionmentioning
confidence: 99%
“…These include (but are not limited to): (1) free fatty acid receptor 1 (FFAR1), FFAR2, FFAR3, and FFAR4, which are activated by free fatty acids; (2) glucagon receptor (GCGR), which responds to glucagon; (3) cholinergic receptor, muscarinic 3 (CHRM3), which is activated by acetylcholine; (4) adrenoceptor beta 2, surface (ADRB2), which is engaged by norepinephrine; and (5) purinergic receptor P2Y, G protein-coupled, 13 (P2RY13), which is responsive to ADP (Wauson et al, 2014). The signal transduction pathways that relay the liganddependent activation of these receptors to the autophagic machinery are heterogeneous but generally involve elevations in the intracellular levels of inositol-1,4,5,-triphosphate and diacylglycerol, or cAMP, which de facto stimulate autophagy via the AMPK/MTORC1 hub (Wauson et al, 2014).…”
Section: Initiation Of Autophagy By the Plasma Membranementioning
confidence: 99%
“…G protein-coupled receptor, class C, group 6, member A (GPRC6A), calcium-sensing receptor (CASR), gamma-aminobutyric acid B receptor 1 (GABBR1), heteromeric taste receptors, and various metabotropic glutamate receptors, all of which are activated by one or several amino acids, share the ability to repress autophagy in the presence of their ligands (Wauson et al, 2014). The molecular cascades connecting these GPCRs to the autophagic machinery are not completely understood but have been proposed to involve G proteins that provoke a decrease in the intracellular levels of cAMP, resulting in the suppression of AMPK activity (Wauson et al, 2014).…”
Section: ''Signal Off'' Pm-driven Autophagymentioning
confidence: 99%
See 2 more Smart Citations